Etika Berbahasa Generasi Z di Platform 'X' - Putri Nur’Aini, Alya; Artika Devi, Neta; Eka Maharani Putri, Silvia; Primakusuma W, Angela; Shafira Ramadhani, Nasywa; Puspa Arum, Dewi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This research aims to examine the evolving dynamics of language ethics among Generation Z, focusing on their communication behaviors on the